O Nicolau II de “Matilda” (2017) : comemoração, tensão e disputas de memória no Centenário da Revolução Russa - Silva, Sidney Junior Martins da (2023)
In 2017, the Centennial of the Russian Revolution would be celebrated in various parts of the world. However, contrary to what one might think at first, the arrival of the date in Russia would not mean a moment of full harmony around the revolution and its celebration. Not even for the Russian government, exalting the memory of 1917 was comfortable, since many wounds from the past remained open in the country, opposing defenders of Lenin and Stalin's regime to radically contrary sectors. In this scenario, the film "Matilda" would be released, provoking controversy in the country. The filmic work, in short, deals with a love story between young Nicholas II (1868-1918), who had not yet been crowned emperor, and a theater dancer, Matilda Kschessinskaya (1872-1971). That said, this dissertation aims to problematize the dimensions of the controversy involved in "Matilda," highlighting, among its objectives, to understand the commemorations surrounding the Centennial of the Russian Revolution in 2017; to investigate the controversies that surrounded the filmic work in the context of the aforementioned commemorations; and to analyze the proposal of the work "Matilda" as it enters the disputes of memory that occurred in the Centennial. To this end, in addition to the main source, the film, we also focused on the search for information in several websites, with greater emphasis on international newspapers and news agencies that dealt with the subject. Finally, based on theoretical and methodological readings related to the work with film, and also to the concepts of memory and history, this dissertation was structured in three chapters.